Evaluation of risk caused by wastewater discharges from the Petrochemical Special Economic Zone (PETZONE) to the Musa Bay (Persian Gulf-Iran) / Ghazaleh Monazami Tehrani - Tehrani, Ghazaleh Monazami (2012)
This study investigated the presence of polycyclic aromatic hydrocarbons (PAHs) and total petroleum hydrocarbon (TPH) in the wastewater effluents of PETZONE and sediments of the Musa Bay (around the PETZONE coastal area) from Jun 2009 to Jun 2010. The primary objectives of this study were to evaluate the sources of pollutants and each pollutant‘s distribution, concentration and contamination degree, as well as to assess the biological response to these stressors based on the ecological risk. The levels of TPH concentration in the study area were found to be relatively moderate (with an average value of 48.98 μg/g) compared to the world-wide chronically oil-contaminated locations. Also the average concentration of PAHs was found to be lower than the guideline values (with a mean value of 3.40 μg/g) in the study area and other parts of the bay. The source analysis based on the isomer pair ratios and also the principle component analysis showed that, in addition to petrogenic input as a major source, pyrolytic inputs are also a source for PAHs. Also, the results of Chronic Potency Ratio of PAHs showed that, all the sampling stations meet the guideline value with the exception of the stations 3-BI and 4 (which are located in the vicinity of the Bandar-e-Imam Khomeini petrochemical company). Furthermore, the contamination factor showed that, the study area can be classified as slightly polluted and be categorized as of low ecological risk. Also, the average value of AMBI was 2.66, so the study area can be categorized as slightly polluted based on this index. Owing to this index, the pollution level of most of the stations varied between undisturbed and moderately polluted (except stations 3-BI and 4). In the case of environmental impact assessment (EIA), the PETZONE effluent outlets were monitored and showed that, the average concentrations of PAHs were lower than the guideline values at all the stations; thus the effluents of the study area can be considered unpolluted. Also, the average concentration of TPH was lower than the guideline value at all sampling stations with the exception of the effluent outlets of Razi and Bandar-e-Imam Khomeini petrochemical companies which are proximal to Musa Bay and they may have an adverse impact on the aquatic ecosystem of the bay. The result of the Risk Priority Number (RPN) based on TPH showed that, Bandar-e-Imam Khomeini petrochemical company can be classified in a category of important environmental aspect, and Razi and Shahid Tondgouyan petrochemical companies can be categorized as moderate environmental aspects; while the rest of the petrochemical companies can be classified as low environmental aspects. Thus, Bandar-e-Imam Khomeini petrochemical company should mitigate the risk and it requires executive management attention and control actions, while, Razi and Shahid Tondgouyan petrochemical companies should plan to manage the risk and decrease it during the long term. In addition, the results of RPN based on PAHs demonstrated that, all the sampling stations can be classified as low environmental aspects, thus more control actions is not necessary but they should be monitored during their activity. Keywords: Ecological Risk, Environmental Impact Assessment, RPN, TPH, PAHs, AMBI, PETZONE, Musa Bay.